Planet, people & prosperity : an exploration of sustainable microfinance practices in South Africa : a case study of the Kuyasa Fund in Cape Town - Larsen, Jenna (Department of Social Development, 2015)
This dissertation explored sustainable microfinance (SMF) practices in South Africa through an investigation of the microfinance sector nationally. Since recipients of microfinance largely depend on local ecosystems and natural resource bases for sustaining livelihoods and improving quality of life (QOL), microfinance has been identified as an important development strategy for reducing the vulnerabilities associated with changing environmental conditions for impoverished people. A framework for SMF consisting of four principles was assembled based on the sustainable development theory and microfinance literature. The qualitative methodology encompassed two main approaches: (1) a literature review that located examples of SMF practices found internationally, which contributed to understanding the concept and provided insights for South Africa and; (2) a case study where a sample of organisations across the country and an in-depth look at one housing microfinance institution (MFI) offered insight into SMF practices. Data was collected from the sample by way of interviews and personal correspondence with key players from eight organisations from four provinces. Data gathered from the housing MFI was through 20 interviews with management, staff, partnering organisations and loan recipients; as well as through direct observation of the loan collections process and by reviewing organisation documents. The main finding was that SMF does not yet exist in practice but that it is emerging although it is not yet recognized by the industry at large. Four organisations were beginning to consider the environment in practice through exposure, awareness, environmental initiatives, renewable energy (RE) and by promoting SMF. The evidence was analysed against the SMF framework, which found that two-thirds (2/3) of the criteria supported the framework while the other one-third (1/3) did not. This suggests that more research is needed; since finding relevant organisations was challenging, the housing MFI was a ‘loose’ fit for the framework where not all aspects of SMF were integrated and the sample organisations were not investigated with enough depth. If sustainability continues to be sacrificed in microfinance practice, it is apparent that loan recipient’s lives and the industry will face many challenges and microfinance runs the risk of becoming another development failure.